Agglomeration and reactivity of nanoparticles of SiO2, TiO2, Al2O3, Fe2O3, and clays in cement pastes and effects on compressive strength at ambient and elevated temperatures. (10th April 2018) - Reches, Yonathan; Thomson, Kate; Helbing, Marne; Kosson, David S.; Sanchez, Florence
Highlights: Instability of SiO2 and TiO2 NP suspensions in alkaline environment. NPs formed microscale agglomerates in the cement matrix. NP agglomeration state in water not indicative of final state in cement matrix. TiO2, bentonite, and halloysite NPs increased compressive strength at 200 °C. Abstract: The agglomeration state of SiO2, TiO2, Al2 O3, Fe2 O3, bentonite, and halloysite nanoparticles (NPs) in solutions, including simulated cement environments, and their agglomeration and reactivity within the cement paste were evaluated. In water, all NPs formed agglomerates, while sonication and addition of polycarboxylate-based, high range water reducer generally decreased the agglomerate size. Agglomeration of NPs was observed in the chemical environment of hydrating cement paste. The bridging role of Ca 2+, charge balancing, screening by K +, and pH were identified as factors controlling agglomeration. TiO2, bentonite, and halloysite NPs enhanced the cement paste residual compressive strength after exposure to elevated temperature.